Anterior Papillary Muscle Rupture due to Acute Myocardial Microinfarction of the Small High Lateral Branch - Takanori Kono; Kazuyoshi Takagi; Shinya Negoto; Eiki Tayama (Case Reports in Cardiology)
Papillary muscle rupture is a catastrophic condition, of which most cases manifest posterior papillary muscle rupture. Anterior papillary muscle rupture is a rare condition. Particularly, anterior papillary muscle rupture due to acute myocardial microinfarction of the small high lateral branch is extremely rare. Since papillary muscle rupture can occur even in such a small branch or small area due to myocardial infarction, echocardiographic and/or ventriculographic confirmation is essential in cases of sudden worsening of heart failure. Herein, we report the case of anterior papillary muscle rupture with a good outcome. A 61-year-old man was admitted to our hospital with cardiogenic shock. Echocardiography revealed severe mitral regurgitation due to papillary muscle rupture. Coronary angiography demonstrated high-grade stenosis in the high lateral branch. However, no other significant stenoses were found. Emergency mitral valve replacement was performed. The patient was discharged 19 days after surgery without any complications.